Incidence of infected hardware removal in oral and maxillofacial region - REDDY, P ADITYA; P U, ABDUL WAHAB; V., JAGADISH (The journal of contemporary issues in business and government, 2021)
Maxillofacial fractures are typically treated with open reduction and internal fixation. Open reduction and internal fixation can be complicated by hardware exposure or infection. The literature often does not differentiate between these 2 entities; so for this study, we have considered all hardware exposures as hardware infections. Approximately 5% of adults with CMF trauma are thought to develop hardware infections. Management consists of either removing the hardware versus leaving it in situ. To evaluate the incidence of infected hardware removal in the maxillofacial region. A retrospective hospital based study,patients undergone for plate removal [hardware] where taken by analyzing and reviewing 86000 patients record ,and searched for chief complaint,patient complaining of pain ,swelling were noted and entered in Our study noted that 22 patients had undergone the hardware removal out of which 68% were symptomatic.18%were plate exposure.13%were according to patients will.:Management of hardware removal needs to be done in sequential and consistent manner in order to bring better outcome.From the data available the incidence of infected hardware removal is relatively low